Propofol-fentanyl bolus versus ketofol continuous infusion for sedation-analgesia in elective colonoscopy - Edwin García García; Idoris Oramas Rodríguez; Juliette Massip Nicot; Víctor Navarrete Zuazo; Bertha Wilson Batista; Dania María Rodríguez Martínez (Revista Cubana de Anestesiología y Reanimación, 2018)
Introduction: Colonoscopy is performed frequently, for which conscious sedation is useful. Objectives: To compare propofol-fentanyl bolus with ketofol continuous infusion for colonoscopy. Methods: A quasi-experimental study was performed in 150 patients divided into two groups. In the propofol-fentanyl group, induction was performed with fentanyl at doses 1.5-3 μg/kg plus propofol at doses 0.5-1.5 mg/kg and maintenance with propofol boluses at doses 0.4-0.5 mg/kg. In the ketofol group, a solution was used as obtained by associating 50 mL of propofol (1%) and 0.5 mL of ketamine (5%); loading dose of 1.1 mg/kg and maintenance with manual continuous infusion. Hemodynamic and respiratory variables were studied, together with sedation level, patient and colonoscopy technician satisfaction, recovery time and adverse events. Results: Mean arterial pressure and SpO2 showed differences between groups and at different times, with lower figures in the propofol-fentanyl group. The heart rate did not vary between the groups. Patients and endoscopy technician satisfaction was high in both strategies. Patients in the propofol-fentanyl group had longer recovery time (27 min.). Less than half of the patients presented adverse events. Pain, dissatisfaction and respiratory depression were the most frequent. Conclusions: Ketofol was higher to the propofol-fentanyl association with better hemodynamic and respiratory stability, more stable sedation levels, patient and gastroenterologist satisfaction, shorter recovery times, limited and mild adverse events.